Alternative Model of Three-Phase Transmission Line Theory-Based Modal Decomposition - Silva, R. C. [UNESP]; Kurokawa, S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
In this paper is shown the development of a transmission line, based on discrete circuit elements that provide responses directly in the time domain and phase. This model is valid for ideally transposed rows represent the phases of each of the small line segments are separated in their modes of propagation and the voltage and current are calculated at the modal field. However, the conversion phase-mode-phase is inserted in the state equations which describe the currents and voltages along the line of which there is no need to know the user of the model representation of the theory in the field lines modal.
Keywords: pi-circuits; electromagnetic transients; transmission lines; transmission line models